2020
DOI: 10.1186/s13287-020-01878-2
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1-modified human umbilical cord mesenchymal stem cells ameliorate experimental peritoneal fibrosis by inhibiting the TGF-β/Smad3 pathway

Abstract: Introduction: Peritoneal fibrosis is a serious complication of long-term peritoneal dialysis (PD). Combination therapies are emerging as a promising treatment for tissue damage. Here, we investigated the therapeutic potential of SIRT1modified human umbilical cord mesenchymal stem cells (hUCMSCs) for peritoneal fibrosis. Methods: SIRT1 was overexpressed in hUCMSCs to establish SIRT1-modified hUCMSCs. Co-culture and transplantation experiments were performed in TGF-β-stimulated Met-5A cells and peritoneal damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Previous studies have revealed that the signaling pathways involved in peritoneal fibrosis are very complex, mainly including the cannabinoid signaling pathway, oxidative stress signaling pathway, TGF-β signaling pathway, NF-kB signaling pathway, Sonic Hedgehog signaling pathway, etc. [ 23 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that the signaling pathways involved in peritoneal fibrosis are very complex, mainly including the cannabinoid signaling pathway, oxidative stress signaling pathway, TGF-β signaling pathway, NF-kB signaling pathway, Sonic Hedgehog signaling pathway, etc. [ 23 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subjects in the control, NaCl and Mannitol groups were intraperitoneally injected with a volume of 25 ml twice daily for 6 weeks. Animals in the PD group were injected continuously for 3 days starting on the second week, with a daily dose of 4.25% PD solution containing 0.5% lipopolysaccharide (50 ml) to promote peritoneal fibrosis 22 . Rats in the AAV group were injected with Adeno-associated virus (AAV) after 2 weeks, and each rat was intraperitoneally injected with 2×10 10 viral genomes.…”
Section: Methodsmentioning
confidence: 99%
“…4.25% HGPDS or PBS was intraperitoneally injected daily into male mice for 4 weeks. The peritoneal equilibration test (PET) was conducted 28 days after PD treatment as previously described [20, 21]. The dialysate creatinine concentration (D), plasma creatinine concentration (P), peritoneal fluid glucose concentration (D0), and peritoneal fluid glucose concentration (D2) were measured.…”
Section: Methodsmentioning
confidence: 99%